Visceral Leishmaniasis Clinical Management in Endemic Districts of India, Nepal, and Bangladesh - Megha Raj Banjara; Siddhivinayak Hirve; Niyamat Ali Siddiqui; Narendra Kumar; Sangeeta Kansal; M. Mamun Huda; Pradeep Das; Suman Rijal; Chitra Kumar Gurung; Paritosh Malaviya; Byron Arana; Axel Kroeger; et al. (Journal of Tropical Medicine)
Background. National VL Elimination Programs in India, Nepal and Bangladesh face challenges as home-based Miltefosine treatment is introduced. Objectives. To study constraints of VL management in endemic districts within context of national elimination programs before and after intervention. Methods. Ninety-two and 41 newly diagnosed VL patients were interviewed for clinical and provider experience in 2009 before and in 2010 after intervention (district training and improved supply of diagnostics and drugs). Providers were assessed for adherence to treatment guidelines. Facilities and doctor-patient consultations were observed to assess quality of care. Results. Miltefosine use increased from 33% to 59% except in Nepal where amphotericin was better available. Incorrect dosage and treatment interruptions were rare. Advice on potential side effects was uncommon but improved significantly in 2010. Physicians did not rule out pregnancy prior to starting Miltefosine. Fever measurement or spleen palpation was infrequently done in Bangladesh but improved after intervention (from 23% to 47%). Physician awareness of renal or liver toxicity as Miltefosine side effects was lower in Bangladesh. Bio-chemical monitoring was uncommon. Patient satisfaction with services remained low for ease of access or time provider spent with patient. Health facilities were better stocked with rK39 kits and Miltefosine in 2010.